The crystal structure of [μ-hydroxido-bis[(5,5′-dimethyl-2,2′-bipyridine-κ2N,N′)-tricarbonylrhenium(I)] bromide hemihydrate, C30H26N4O9Re2Br - Moherane Lehlohonolo; Alexander Orbett T.; Visser Hendrik G.; Manicum Amanda-Lee E. (Zeitschrift für Kristallographie - New Crystal Structures)
C30H26N4O9Re2Br, triclinic, P1‾$P\bar{1}$ (no. 2), a = 9.407(6) Å, b = 11.769(8) Å, c = 15.055(11) Å, α = 82.70(2)°, β = 76.68(3)°, γ = 77.364(2)°, V = 1577.5(19) Å3, Z = 2, Rgt(F) = 0.0291, wRref(F2) = 0.0868, T = 100 K.